Factors Affecting Knowledge and Adoption of Preventive and Control Measures of Diseases among Goat Owners under Field Condition - Rakesh Roy and Rupasi Tiwari, (Indian Journal of Extension Education, 2023)
Disease prevention is more economical than treatment and some diseases cannot be treated. Consideringthis factor the present study was taken up with the objective to assess knowledge and adoption level ofpreventive and control measures of diseases and factors affecting in knowledge and adoption among goatowners under field condition. The study was purposively conducted in West Bengal and Uttar Pradesh onthe basis of high goat populated state in the country. In all, 180 respondents were randomly selected for thestudy. The study shows that majority of the respondents had knowledge of keeping feed and water troughclean and had adopted this practice. Disinfection of shed at least once in a week and isolation of healthyanimals from sick animals was not known to majority of the respondents and therefore majority had notadopted this practice. Vaccination as preventive and control measure of diseases in goat was known tomajority of the respondents even through the adoption of this practice was low. Proper disposal of carcassand litter was known to majority of the respondents thereby majority had fully adopted these practices.None had knowledge on quarantine of newly purchased animals, use of footbath and rotational grazing andthus adoption to these practices were nil. The study also shows that goat owners had medium level ofknowledge but had low level of adoption. The study revealed that education, flock size, farming experience,mass media exposure, formal interpersonal contact and social participation had significant and positiveassociation with knowledge level similarly education, family education status, knowledge level, mass mediaexposure, formal interpersonal contact and social participation had significant and positive association withadoption. The study further revealed that education and farming experience of the respondents were maincontributing factors for knowledge level in preventive and control measures of diseases and knowledgelevel, mass media exposure, income in goat farming and annual family income were the main contributingfactors in adoption of preventive and control measures of diseases.